Approximation of conjugate differentiable functions by their Abel–Poisson integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain the exact values of upper bounds of approximations of classes of periodic conjugate differentiable functions by their Abel–Poisson integrals in uniform and integral metrics.